Fermentation-based biotransformation of bioactive phenolics and volatile compounds from cashew apple juice by select lactic acid bacteria. (August 2017) - Kaprasob, Ratchadaporn; Kerdchoechuen, Orapin; Laohakunjit, Natta; Sarkar, Dipayan; Shetty, Kalidas
Graphical abstract: Highlights: Bioactive phenolics and vitamin C of cashew apple juice were enhanced by fermentation. Fermentation-based biotransformation maintains the antioxidant activity of cashew apple. Fermented cashew apple juice enhanced the whiskey and acid flavor volatiles. Abstract: Select lactic acid bacteria (LAB); Lactobacillus plantarum, L. casei and L. acidophilus were targeted for enhancing bioactives and flavor volatiles of cashew apple juice (CAJ) that is an underutilized byproduct from cashew nut processing in Tropical countries. Results indicated the vitamin C and phenolic metabolites such as condensed tannin can be increased at certain stages such as at 12 h over the 48 h fermentation period. Whereas antioxidant activity based on DPPH and ABTS radical scavenging activity generally decreased from initial unfermented stage range of (75%–95%) to consistently in the 50% range by 48 h of fermentation and this follows the decrease in viable counts. The fermentation process increased the condensed tannin contents in CAJ whereas hydrolysable tannins decreased. In this study the changes in flavor volatile types were also analyzed over the course of CAJ fermentation. The results indicated that LAB changed the flavor profiles of fermented CAJ and overall the fruity odor decreased, but the whiskey and acid odor increased. These results provide the foundation to further target the functional benefits of LAB-induced fermented CAJ for further human, animal, and plant health applications.